Routes through exile and memory: The War of Resistance (1937–45) and displacement in Chinese art and literature - FitzGerald, Carolyn Michelle (ProQuest Dissertations & Theses, 2007)
This dissertation examines art and literature produced by intellectuals displaced in China during the War of Resistance (1937-45), a period when tens of millions of people fled from coastal urban areas to the southwest. Showing that the war was a time of cultural ferment characterized by interaction between writers and artists from around the country, it argues that massive displacement fostered cross-generic formal experimentation in all fields of art and literature. Also, as intellectuals traveled to the interior and produced works about new settings and subjects for changing audiences, often of different class backgrounds, they were forced to perform shifting gendered roles as artists. In order to better understand this tumultuous historical milieu and intellectuals' interdisciplinary experiments, this project analyzes works from different genres, including visual art, drama, poetry, film, and fiction. Moreover, rather than focusing on the traditional division of wartime culture into three separate regions-Japanese, Nationalist, and C.C.P. controlled-it looks at the routes taken by intellectuals through these perpetually shifting areas. Although wartime culture was the product of upheaval and fluidity of boundaries, it paradoxically also witnessed a revival of tradition. Traveling from Westernized urban cities towards the southwest hinterland, intellectuals envisioned themselves moving towards China's past and conceived of the rural as the site of national authenticity. In addition, they sought to construct "national forms" by appropriating from myth, legend, and traditional forms in collective memory. Generally, this wartime revitalization of tradition has been interpreted as the product of popularization of culture, engineered by left-wing intellectuals and the C.C.P. However, this dissertation traces intellectuals' root-seeking efforts through a wide variety of both popular and elite works. In doing so, it contends that these trends should be understood in part as a reflection of intellectuals' yearning to reconstruct cultural identities shattered by the upheaval of war. In contrast to previous studies that interpret wartime culture predominantly within left-wing ideology, this study thus presents a view of it as emerging from historical conditions of wartime displacement that created an uneasy tension between various forms of cultural border crossing and the search for national roots.